Contextual Teaching Learning Untuk Peningkatan Pembelajaran Bahasa Arab - Auriel Zaeni, Rahmania; Fahrudin Nur, Muhammad; Wahab Rosyidi, Abdul; Mufidah, Nuril (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study aims to examine the importance of implementing Contextual Teaching and Learning (CTL) in Arabic language learning through the Systematic Literature Review (SLR) method. The researcher analysed 30 relevant journal articles, published between 2018 to 2023, related to the effectiveness of CTL in improving Arabic language skills. The results showed that the application of the CTL method, which links learning materials to students‘ daily lives, proved effective in improving students’ learning outcomes, speaking, writing and Arabic vocabulary skills. Various studies show significant improvements in students‘ understanding of the material and academic achievement after the implementation of CTL, despite some challenges, such as limited facilities and differences in students’ abilities. The findings from this study show that despite the obstacles in its implementation, CTL can have a positive impact on Arabic language learning, both at the primary, secondary and tertiary levels. Therefore, CTL becomes one of the important approaches in Arabic language learning that should continue to be developed and implemented well